if (-1) is a zero of the polynomial p(x) =kx^3-x^2+x+4​

Question

if (-1) is a zero of the polynomial p(x) =kx^3-x^2+x+4​

in progress 0
Madeline 3 weeks 2021-11-07T10:44:16+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-11-07T10:45:56+00:00

    Step-by-step explanation:

    if -1 is a zero of the polynomial kx^3-x^2+x+4,then p (-1) = 0

    0 = k × (-1^3) – (-1^2) + (-1) + 4

    0 = k×(-1) – 1 – 1 + 4

    0 = -k – 1 – 1 + 4

    k = -2 + 4

    k = 2

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )